Penataan Kampung Kota Melalui Pendekatan Partisipatif di Bantaran Sungai Code, Yogyakarta: Studi Kasus: Kampung Gemblakan Bawah, Kelurahan Suryatmajan, Kota Yogyakarta - Febriatmo Teguh Prakoso; Paulus Bawole (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2022)
Title: Urban Kampung Re-Arrangement in Code Riverbank Yogyakarta through Participatory Approach; Case Study: Kampung of Gemblakan Bawah, Suryatmajan Sub-district, Yogyakarta City Sub-district Suryatmajan is one of the slum areas in Yogyakarta. The settlements along the Code riverbanks, Suratmajan Sub-district have various problems such as high population density, irregular buildings setting, environment drainage/sewerage, being prone to fire, flood, cold lava overflow from Merapi Volcano, and other disasters. The Penataan Lingkungan Permukiman Berbasis Masyarakat (PLPBK) program, continued with the Kota Tanpa Kumuh (Kotaku) program, as attempts to overcome these problems with participatory approach. This study aims to explain the implementation of the settlement re-arrangement program through community participation along the Code Riverbank, Kampung Gemblakan Bawah, Suryatmajan Sub-district, Danurejan District, Yogyakarta. The concepts of settlement re-arrangement, sustainable development, and community participation are the analytical tools for achieving the research objectives. This research is a qualitative descriptive study with primary data from interviews, observations, and documentation, supported by some secondary data. The results of the PLPBK program, followed by the Kotaku program through a participatory approach, can be seen in infrastructure changes and changes in mindset and behavior. The impact of this settlement re-arrangement related to socio-cultural, environmental, and economic aspects. In the implementation of the program, the elements of participation are fulfilled. The form of community participation in the program is authentic participation with a level of support for independent community interests. Furthermore, the concept of communication that is carried out in stages through the role of leaders and the community participation in submitting opinions can be seen as the participatory approach of this program.